SPECIFICITIES AND LEGISLATIVE LANDMARKS OF CORPORATE GOVERNANCE IN ROMANIAN PUBLIC INSTITUTIONS - Mitrache Daniel-Marius (Annals of the University of Craiova: Economic Sciences Series)
A corporate governance system within the specific economic landscape of Romania would need a unique approach that differentiates between the public and private sectors, taking into account the peculiar characteristics of the transition to a market-oriented economy, together with consideration for the legislative context in Romania and compatibility with international corporate governance standards, mostly the European model, in light of which the Romanian economy should adapt and transform. It is important that the domestic legislative provisions on corporate governance, which particularly concern public enterprises, are known and corroborated, in the process of their implementation, with the European directives on the matter. The organization, functioning and governance of public enterprises must be based on principles compatible with a competitive economy. The process of aligning the corporate governance of public enterprises with European structures and principles involves, in particular, the prior auditing of these enterprises. In Romania, this auditing process is grounded in principles reflective of the transition towards a competitive market economy, emphasizing the creation and maximization of value. This is a condition to ensure their functional compatibility with the corporate environment in the European and global integrationist context.